Stress and vibration analysis of curved beams using ANSYS finite element software - Kalaichelvan, Thurga (Nanyang Technological University, 2024)
This report presents the findings of the final year project about the stress and vibration analysis of curved beams using finite element software. Mesh convergence studies were conducted to determine the optimal mesh to be used for the analysis. The optimal mesh obtained from the mesh convergence studies were used for the parametric study of curved beams. In static analysis, the downward displacement and von Mises stress at the mid-section of the curved beam were computed. In vibration analysis, natural frequencies and mode shapes were computed. Load carrying capacities of the curved beam was also analyzed by varying the breadth of the beam and height of the arc of the beam. These analyses were replicated for the straight beam as well, so that the performance of the curved beam can be compared with that of the straight beam. The results of this study reveal that the load carrying capacity of curved beams is much higher than that of the straight beam. It is also observed that the load carrying capacity of a curved beam increases with the breadth of the beam and even more so with the height of curvature of the beam.